2020
DOI: 10.1177/1477370820931867
|View full text |Cite
|
Sign up to set email alerts
|

Women police leaders in Europe: A tale of prejudice and patronage

Abstract: This article provides rich and unique insights into the experiences of women police leaders across seven European regions. Drawing on interview data, it presents accounts of women’s experiences in policing and identifies informal and formal barriers to their advancement in European police organizations. Women police leaders report high levels of gender discrimination, obstruction and prejudice over the course of their careers. We argue that there are a number of subjective and informal criteria of ‘acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…On the basis of the theoretical framework and especially in the research carried out by Natarajan (2008) and Silvestri and Tong (2020) , concerning to the differentiated conditions faced by men and women in the workplaces, the results of the study are shown in four main themes as follows: (1) Perceived Representation (adequate representation and supporting female quotas); (2) The perceived nature of police work (police relevant competences, physical strength required and work-life balance); (3) Perceived organizational structure of law enforcement and the police subculture (male police subculture and perceived discrimination); and (4) Perceived stereotyping of female police officers (female specific skills, motivation, capacity and strength and female specific organizational barriers). Results are described in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of the theoretical framework and especially in the research carried out by Natarajan (2008) and Silvestri and Tong (2020) , concerning to the differentiated conditions faced by men and women in the workplaces, the results of the study are shown in four main themes as follows: (1) Perceived Representation (adequate representation and supporting female quotas); (2) The perceived nature of police work (police relevant competences, physical strength required and work-life balance); (3) Perceived organizational structure of law enforcement and the police subculture (male police subculture and perceived discrimination); and (4) Perceived stereotyping of female police officers (female specific skills, motivation, capacity and strength and female specific organizational barriers). Results are described in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the role of the policeman has been played by men and the result is that, not only has their effectiveness or capabilities not been questioned, but the erroneous conclusion, never empirically endorsed, has been reached that the qualities required to be a good policeman are those that are stereotypical of male culture exclusively ( Lanier, 1996 ; Archbold et al, 2010 ; Van Laar et al, 2017 ). Thus, despite the gradual integration of women into the police forces, first by carrying out auxiliary tasks and, progressively, in more operational tasks, it may be that the career development of women is mediated by formal and informal barriers and obstacles linked to gender and organizational culture ( Silvestri and Tong, 2020 ).…”
Section: Theoretical Framework: Barriers and Controversies Over Female Police Officers In The Workplacementioning
confidence: 99%
See 3 more Smart Citations